The sworn virgin : a novel - Dukes, Kristopher (William Morrow, an imprint of HarperCollinsPublishers, 2017)
When Eleanora's father is shot dead on the cobblestone streets of 1910 Albania, she must abandon her dreams and struggle to survive in a remote mountain village with her stepmother Meria. Nearing starvation, Meria sells Eleanora into marriage with the cruel heir of a powerful clan. Intent on keeping her freedom, Eleanora takes an oath to remain a virgin for the rest of her life-- a tradition that gives her the right to live as a man: she is now head of her household and can work for a living as well as carry a gun. When an injured stranger stumbles into her life, Eleanora nurses him back to health, saving his life-- yet risking her own as she falls in love with him.